KEBIJAKAN INDIA MENAHAN DUTA BESAR ITALIA UNTUK INDIA PADA INSIDEN ENRICA LEXIE TAHUN 2013 - Almuhtadie Billa; Yuli Fachri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The conflict between India and Italy were preceded by shooting two Indian fishermen by Italian marines take legal complex. This was caused by the second argument Country conflicting legal process that must be taken by the two Italian marines. Various ways taken by Italy to repatriate the two marines on health grounds. Italy struggles to repatriate the two marines was a good response from the Indian government after some diplomacy pursued by Italy. The Italian government does not restore the two marines to India. This provoked a strong reaction in India, Government of India condemned the action taken by the Italian Government. Daniele Mancini, as envoy Ambassador of Italy to India earlier guarantee the return of Italian marines on bail him that the two marines would return to India after the existing agreement. But an agreement is violated by Italy, this led to Daniele Mancini held in India with not allowed to leave India as collateral itself on the Italian marines. Keywords: Italy, India, Enrica Lexie, Conflict, Ambassador, Marines, Foreign Policy, Diplomacy.